Analisis Yuridis Terhadap Denda Piutang Iuran BPJS Ketenagakerjaan Yang Tidak Dibayar Oleh Perusahaan Yang Terdaftar (Studi di BPJS Ketenagakerjaan Kabupaten Labuhan Batu Selatan) - Muhammad Haris; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2019)
Abstract : In the implementation of payment of the Manpower Social Security Organizing Agency (BPJS), the employer is obliged to pay contributions on time in accordance with the program being followed. If the participating companies are late or in arrears in payment of the Employment Social Security Agency (BPJS) contributions, they may be subject to a fine of 2% (two percent) of the total contributions of the Employment Social Security Agency (BPJS) of Employment that must be paid by the employer company that has already been paid registered. In its implementation in South Labuhanbatu Regency, payment of contributions and fines of the Social Security Organizing Agency (BPJS) of Manpower are not carried out entirely by registered companies. Employers/companies only pay contributions from the Social Security Organizing Agency (BPJS) in arrears without paying fines, but strangely enough the Employee Social Security Organizing Agency (BPJS) must continue to receive payment in arrears without any delay, even though it is worth knowing the State income. in the sector of the Social Security Organizing Agency (BPJS) the employment is reduced. Non-compliance in paying contributions due by employer companies to the Social Security Organizing Agency (BPJS) can continue to occur due to unclear legal consequences for registered companies. As for the problems arising, namely: regarding legal certainty of the imposition of fines on contributions from Manpower Social Security Organizing Agency (BPJS) for Labor; legal consequences for the participating companies if the Manpower Social Security Agency (BPJS) contribution receivable penalties are not paid; and barriers to collection of contribution fines for receivables from the Social Security Organizing Agency (BPJS) of Branch Office (KCP) Labuhanbatu Selatan Pinang City as well as the efforts that have been made. Keywords : fee receivable fines; social security organization of employment; and participating companies